Overview of radiotracer experiments for better understanding of wastewater and water treatment plants in Lima (Perú) - Sebastián Calvo, Carlos (2018)
The objectives of this paper are to present an overview of possible applications of the radiotracers for better understanding of water and wastewater treatment plants. Numerous experiments have been carried out in different plants located in Lima. Four processes have been investigated: desanders, flocculators, clarifiers and digesters. Depending on the studied process, the experimental results have been interpreted at different levels of complexity: from simple troubleshooting to the modeling of the flow behavior inside the process.